(3GdYhGed GdLOjOI aj GdfMhs - (3GdLQLGfj, GdCTYQj, GdTGaYj, CHh HcQ, YHO GdbGgQ Hf YHO GdQMef Hf eMeO, (B471 (3g`s ((3SdGe Hf YHO Gddgs)
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeGFg GdTGedIhGYde Cf GdYhGed aj GdfMh Ydi eG Cdag GdTjNYHO GdbGgQ Hf YHO GdQMef GdLQLGfjeGFI YGed daXjI heYfhjIs
(3BNQgG (B:s
(3agPg eGFI YGed dG jSJZfj GdUZjQ hGdcHjQ hGdhVjY hGdQajY Yf eYQaJgG hGSJYeGdgG JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 48s
(3eYLe GdeDdajf(B: 2 / 201s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs